Multi‐scale classification of fluvial architecture: An example from the Palaeocene–Eocene Bighorn Basin, Wyoming. Issue 6 (18th April 2017) - Owen, Amanda; Ebinghaus, Alena; Hartley, Adrian J.; Santos, Maurício G. M.; Weissmann, Gary S.
Abstract: Fluvial channel geometry classification schemes are commonly restricted in relation to the scale at which the study took place, often due to outcrop limitations or the need to conduct small‐scale detailed studies. A number of classification schemes are present in the literature; however, there is often limited consistency between them, making application difficult. The aim of this study is to address this key problem by describing channel body geometries across a depositional basin to ensure that a wide range of architectures are documented. This was achieved by studying 28 locations over 4000 m of vertical succession in Palaeocene‐aged and Early Eocene‐aged deposits within the Bighorn Basin, Wyoming, USA. Five different channel body geometries have been defined based on the external geometric form, and internal arrangement and nature of storey contacts. These include the massive channel body geometry, semi‐amalgamated channel body geometry, internally amalgamated channel body geometry and offset stacked channel body geometry, which are considered to be subdivisions of the sheet geometry of many other classifications. An isolated channel body geometry has also been recognized alongside splay channel and sheet sandstone geometries in the floodplain facies associations. Field evidence, including the stacking style of storey surfaces, suggests that the different geometries form a continuum. The nature and degree of amalgamation at the storey scale are important in producing the different geometries and are related to the degree of channel migration. It is speculated that this is the result of differences in sediment supply and available accommodation. In contrast to previous schemes, the classification scheme presented here recognizes the importance of transitional geometries. This geometrical range has been recognized because of the basin‐scale nature of the study.